Redefining the Role of Lymphotoxin Beta Receptor in the Maintenance of Lymphoid Organs and Immune Cell Homeostasis in Adulthood - Shou, Yajun; Koroleva, Ekaterina; Spencer, Cody M.; Shein, Sergey A.; Korchagina, Anna A.; Yusoof, Kizil A.; Parthasarathy, Raksha; Leadbetter, Elizabeth A.; Akopian, Armen N.; Muñoz, Amanda R.; Tumanov, Alexei V. (Frontiers in Immunology, 2021)
Lymphotoxin beta receptor (LTβR) is a promising therapeutic target in autoimmune and infectious diseases as well as cancer. Mice with genetic inactivation of LTβR display multiple defects in development and organization of lymphoid organs, mucosal immune responses, IgA production and an autoimmune phenotype. As these defects are imprinted in embryogenesis and neonate stages, the impact of LTβR signaling in adulthood remains unclear. Here, to overcome developmental defects, we generated mice with inducible ubiquitous genetic inactivation of LTβR in adult mice (iLTβRΔ/Δ mice) and redefined the role of LTβR signaling in organization of lymphoid organs, immune response to mucosal bacterial pathogen, IgA production and autoimmunity. In spleen, postnatal LTβR signaling is required for development of B cell follicles, follicular dendritic cells (FDCs), recruitment of neutrophils and maintenance of the marginal zone. Lymph nodes of iLTβRΔ/Δ mice were reduced in size, lacked FDCs, and had disorganized subcapsular sinus macrophages. Peyer`s patches were smaller in size and numbers, and displayed reduced FDCs. The number of isolated lymphoid follicles in small intestine and colon were also reduced. In contrast to LTβR-/- mice, iLTβRΔ/Δ mice displayed normal thymus structure and did not develop signs of systemic inflammation and autoimmunity. Further, our results suggest that LTβR signaling in adulthood is required for homeostasis of neutrophils, NK, and iNKT cells, but is dispensable for the maintenance of polyclonal IgA production. However, iLTβRΔ/Δ mice exhibited an increased sensitivity to C. rodentium infection and failed to develop pathogen-specific IgA responses. Collectively, our study uncovers new insights of LTβR signaling in adulthood for the maintenance of lymphoid organs, neutrophils, NK and iNKT cells, and IgA production in response to mucosal bacterial pathogen.